Yield, nutrient uptake and economics of soybean under different weed management practices - Singh, S. P.; Singh, J.P.; Bhatnagar, Amit; Kumar, Amit; Yadav, Ajit; Gupta, Gaurendra; Kumari, Usha; Verma, Gaurav (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif season of 2014 at GBPUAT, Pantnagar (Uttarakhand) to find out the effect of integrated weed management options on soybean. The experiment was laidout in a randomized block design with four replications to evaluate ten treatments viz. Preemergence application of herbicide, sulfentrazone 48% SC @ 300 g a.i/ha, sulfentrazone 48% SC @ 360 g a.i/ha, sulfentrazone 48% SC @ 360 g a.i/ha + hand weeding (HW) at 40 (DAS) days after sowing, sulfentrazone 48% SC @ 300 g a.i/ha + HW at 40 DAS, pendimethalin 30 EC @ 750 g a.i/ha, pendimethalin 30 EC @ 1000 g a.i/ha, pendimethalin 30 EC @ 750 g a.i/ha + HW at 40 DAS and pendimethalin 30 EC @ 1000 g a.i/ha +HW at 40 DAS, weed-free and weedy check. Weed-free plot recorded higher grain yield (2.99 t/ha) followed by pre-emergence application of sulfentrazone 48% SC @ 360 g a.i/ha + HW at 40 DAS. The highest nutrient (NPK) uptake (255.2, 37.2, 110.6 kg/ ha) by crop was recorded under weed-free plot treatment. The highest net returns (Rs 49,037/ha) and benefit: cost ratio (1.76) were recorded under pre-emergence application of sulfentrazone 48% SC @ 360 g a.i/ha + HW at 40 DAS. Thus, it could be concluded that pre-emergence application of sulfentrazone 48% SC @ 360 g a.i/ha + HW at 40 DAS can be used for effective weed control in soybean.